THE STUDENTS’ ABILITY IN TRANSLATING TEXT OF ARTS COLUMN IN NEWS WEEK MAGAZINE BY USING DETERMINING SENTENCE DIFFICULTY - Apriana Diana (Journal Of Language Education and Development (JLed), 2022)
Language is very essential for human being. By using language, we can communicate between one another. The everyday use of this term involves several different senses, which linguistics is careful to distinguish. At its most specific level, it may refer to the concrete act of speaking, writing, or signing in a given situation-the notion of parole, or performance. Objective. To know the students’ ability in translating text of Arts column in News Week Magazine by using Determining Sentence Difficulty and To describe the errors made by the students in translating text of Arts Column in News Week Magazine by using Determining Sentence Difficulty. Sample, The research project will be carried out in Muhammadiyah University of North Sumatera, in Faculty of Teacher Training and Education of English Department at the 6th semester. Total sample 149 respondences. Design of research, The research will apply a descriptive quantitative research model. Applying this model is due to the facts that data in this research basically a static or quantitative data that is based on the students’ ability in using Determining Sentence Difficulty. Data analysis, The following procedure will be implemented to analyze the data, Scoring the students’ answer the researcher can make sure that the students’ understand or able to translate the text. Calculating. Percentage Scores = (Total Scores)/(Total Item Test) x 100%. Conclusions, The translating text of Arts column in News Week Magazine by using Determining Sentence Difficulty are effective to use by the students